F187. Cortico-muscular interaction during a tonic muscle contraction - Vial, Felipe; Srivastava, Anshul; Song, Xiao; Horovitz, Silvina; Walitt, Brian; Popa, Trian; Hallett, Mark (Clinical neurophysiology, 2018)
Prolonged voluntary muscle activity leads to a series of changes within the muscles, the nervous system, and the nervous-muscular interaction that can lead to a state called fatigue, defined as the loss of the muscle capability to generate a particular amount of force. The purpose of this study was to characterize the changes in the cortico-muscular interaction before fatigue. Five healthy volunteers participated. Baseline corticospinal excitability was assessed with transcranial magnetic stimulation (TMS) recruitment curves recorded from the dominant motor cortex (M1) and three muscles of the dominant arm (opponens pollicis brevis, flexor digitorum superficialis, and extensor digitorum communis). The exercise consisted in a hand grip of a dynamometer with visual feedback set to 50% of maximum voluntary force for each subject. The grip alternated with rest in blocks of 30 s each. The subjects were required to do as many cycles as they could. The exercise was stopped when the subject was not able to maintain 50% of maximum voluntary force for more than 3 s or after 30 min. During the 30 s rest periods between the contraction cycles, the cortical excitability was assessed with 6 TMS pulses delivered at the intensity corresponding to the middle of the TMS recruitment curve (S50). EEG was also recorded throughout the experiment with a 32-channel EEG cap in a 10–20 montage. The muscle-related changes were quantified with the maximum muscle response (recorded as the Mmax wave) to peripheral stimulation before and after the exercise. Two subjects became fatigued before the 30 min, the other 3 completed the task. From one cycle of contraction to the other, there was a consistent pattern of increase in the root mean square of the EMG amplitude that was coupled with a decrease in the mean frequency. During the rest periods, there was a post-exercise facilitation expressed as increase in MEP sizes that progressively decreased without reaching baseline at the end of the 30 s. There was also a progressive increase in M1 excitability through the cycles. There was no change in Mmax after the exercise. In order to be able to sustain the same amount of force in time, there is a change in the muscle pattern of activation characterized by an increase in amplitude together with a decrease in frequency. The fact that there was not any decrease of M response after the exercise shows that muscle contraction capacity was intact. The changes observed in the EMG pattern might originate at a spinal and/or cortical level. In fact, in this experiment, we did observe an increase in M1 excitability after each muscle contraction cycle and through the cycles. The results are consistent with the concept that muscular fatigue is, at least in part, cortically derived.